Biomarker evidence of the water mass structure and primary productivity changes in the Chukchi Sea over the past 70 years - Gao, Chao; Ruan, Xiaoyan; Zhang, Yi Ge; Yang, Huan; Xiao, Xiaotong; Lü, Xiaoxia; Yang, Yi; Wang, Hongmei; Yu, Xiaoguo (Frontiers in Marine Science, 2023)
The Chukchi Sea has experienced significant changes under global warming in the Common Era, including the shift of primary productivity. However, modern observations are too short to fully investigate the effects of environmental changes in this area. Here, we analyzed lipid biomarkers (e.g. long-chain n-alkanes, n-alkanols, n-alkanoic acids, diols, and sterols) from a sediment core (R07) collected from the Chukchi Sea Shelf to determine phytoplankton primary productivity variations and factors influencing these changes over the past 70 years. Similar trends of the abundance of terrestrial ecosystem-derived compounds (e.g. long-chain n-alkanes, n-alkanols, n-alkanoic acids, and C32 1,15-diol) indicate that terrigenous input increased from ca. 1946 towards ca. 1983 and then decreased thereafter. In comparison, biomarkers with marine origin indicate that the ratio of diatoms to dinoflagellates increased after ca. 1983 towards the core-top (ca. 2011). Concurrent changes in terrigenous input and phytoplankton community indicated a shift in water mass structure at ca. 1983 (i.e. the Alaska Coastal Water decreased and the Bering Sea Water increased), which may be attributed to the phase shift of the Arctic Oscillation and/or unsynchronized flow changes in different water masses. Owing to the different water mass properties, the change of water mass structure caused intense water mixing and the resulting high turbidity in the study area, which led to light limitation for phytoplankton growth. These conditions probably account for the reduced phytoplankton primary productivity from ca. 1983 to ca. 2000 in the general trend of increasing. The results indicate that, in addition to global warming and sea ice retreat, other factors, such as change in regional water mass structure (i.e. different water masses), may also have a significant influence on the primary productivity and the phytoplankton community in the Chukchi Sea Shelf.